ZOOTECHNICAL PERFORMANCE EVALUATION OF THE USE OF BIOFLOC TECHNOLOGY IN NILE TILAPIA FINGERLING PRODUCTION AT DIFFERENT DENSITIES - Rafael Bittencourt Vieira; Leopoldo Melo Barreto; Karina Zanoti Fonseca; Mauricio Santana Lordelo; Fabiana Ribeiro de Souza; Norma Suely Evangelista-Barreto (Boletim do Instituto de Pesca)
The effect of producing and culturing Nile tilapia (Oreochromis niloticus) fingerlings in biofloc technology (BFT)-based systems was investigated in terms of zootechnical performance, aiming to define the best culturing density for 64 days. A completely randomized design was used, with four replications totaling 24 experimental units. The weight gain of each batch of animals per experimental unit (E.U.) was evaluated at densities of 200, 400, 600, 800, and 1,000 fingerlings m-3. For controls, a Water Recirculation System with 248 fingerlings m-3 was used. The fingerlings were fed commercial feed containing 35% protein and brown sugar as a carbohydrate source at a C:N ratio of 20:1. Dissolved oxygen, total ammonia nitrogen, pH, and temperature were monitored daily, and nitrite and alkalinity were monitored weekly. The analysis of weight gain data obtained a linear function y = - 0.0017X2 + 3.724X – 87.77, with r2 = 0.864, coefficient of variation = 14.23%, and correlation coefficient = 0.91. At the end of the cultivation period the system’s planktonic community presented high diversity, dominated by rotifers and diatoms. The data of survival, density management demand, and physicochemical parameters variations of the water suggested an optimal density of 800 fish m-3, since this resulted in an average weight gain per E.U. of 1,891.25 ± 151.24 g, with a productive efficiency index of 274.96 that is approximately three times that of the control treatment (87.43). Biofloc technology can be employed in two-phase super-intensive Nile tilapia culture systems, with a stocking density in the rearing stage of 800 fish m-3.